Correlation between ISQ and Insertion Torque values using double acid-etched implants - Sebastián Gallardo; María Constanza Ibañez; Juan Carlos Ibañez (Journal of Osseointegration, 2016)
Aim The purpose of this study was threefold: (1) to consider whether there was a correlation between stability quotient values (ISQ) and insertion torque values (IT) at implant placement (2); to determine which of these values were more related to success or failure; and (3) to determine the influence of bone type and implant length, diameter and shape in the study results. Materials and methods A retrospective clinical study was carried out between June 2012 and June 2014. The insertion torque and resonance frequency values of 279 double achid etched implants (Osseotite, Biomet 3i, Implant Innovations Inc., Palm Beach Gardens, USA), with conical and parallel walls, and of different diameters and lengths, were tested at the moment of insertion in 90 patients of different age (18-82 years of age/ average: 60.89 years) and of both genders (58 females and 32 males). Collected data were processed and subjected to statistical analysis. Results The mean ISQ value was 70.54, showing no statistical significance between successful and unsuccessful implants. The mean IT value was 44.18. In this case, the values obtained showed a difference between successful and unsuccessful implants, yet not statistically significant (p> 0.05). However, statistically significant differences were found in relation to bone type, shape and length of the implants in IT as well as ISQ values. In the former case (IT values), the differences were only related to diameter. Conclusion There was a correlation between ISQ and IT values; with no significant difference concerning success or failure. The variables analyzed showed statistical differences, except for diameter, which was only significant for IT.